2021
DOI: 10.1155/2021/5170496
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of miR-520b on Macrophage Polarization and T Cell Immunity by Targeting PTEN in Breast Cancer

Abstract: Background. Breast cancer is the most common cancer in women. miR-520b had binding sites with PTEN through the bioinformatics prediction. But few studies have been conducted on miR-520b and PTEN in breast cancer. We aimed to explore the effect of miR-520b and PTEN on breast cancer and the mechanisms involved. Methods. Clinical samples of breast cancer were collected. Bioinformatics analysis was performed to screen the differentially expressed miRNAs. CD4 T cells and CD8 T cells were cocultured with MCF-7 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In addition, PTEN inhibits the differentiation of B cells into plasma cells by regulating PI3K Signal transduction ( Calderón et al, 2021 ). Zhu et al (2021) found that miR-520b targeting PTEN promoted the polarization of M0 macrophages toward M2 in breast cancer. BCL6 promotes the differentiation of B cells into plasma cells by inducing the production of Blimp-1 ( Alinikula et al, 2011 ; Yasuda et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PTEN inhibits the differentiation of B cells into plasma cells by regulating PI3K Signal transduction ( Calderón et al, 2021 ). Zhu et al (2021) found that miR-520b targeting PTEN promoted the polarization of M0 macrophages toward M2 in breast cancer. BCL6 promotes the differentiation of B cells into plasma cells by inducing the production of Blimp-1 ( Alinikula et al, 2011 ; Yasuda et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other pertinent up-regulated miRNAs of interest on this elagolix-treated array include miR-1205, acting like a tumor suppressor by inhibiting KRAS [79]. KRAS mutations play an important role in endometriosis invasion and pathogenesis [26,80]. Mir-520b targets PTEN in breast cancer cells and inhibits T cells and NK cells, and transforms macrophages toward the M2 type [81] and inhibits endothelial activation by targeting NF-kB transcription factor P65, and inflammation [82].…”
Section: Discussionmentioning
confidence: 99%
“…and Zhang et al. 87 , 88 miR-99a breast tumor ↓ breast sera ↓ mTOR PI3K/Akt/mTOR Th17 ↓, Treg ↑ Warth et al. and Qin et al.…”
Section: The Effect Of Secretome On Treg/il-17-producing Treg/th17 Ce...mentioning
confidence: 99%